2004
DOI: 10.1007/s11914-004-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex and ethnic differences in bone architecture

Abstract: Technologic developments and applications such as dual energy x-ray absorptiometry, magnetic resonance imaging, and computed tomography have enabled researchers to assess bone quantity (ie, bone mineral density) and bone quality (ie, bone architecture), which are two important and independent contributions to bone strength. Recent studies on sex differences in bone architecture indicate that a number of biomechanical variables lead to increased bone strength in males compared with females. Ethnic differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…fracture are well known and may be attributable to many factors such as bone structure, genotype or lifestyle (Nelson and Megyesi, 2004;Lei et al, 2006). Other epidemiological data provide some weak evidence that fracture incidence was related to higher protein intake.…”
Section: ~20-40 1 Weekmentioning
confidence: 99%
“…fracture are well known and may be attributable to many factors such as bone structure, genotype or lifestyle (Nelson and Megyesi, 2004;Lei et al, 2006). Other epidemiological data provide some weak evidence that fracture incidence was related to higher protein intake.…”
Section: ~20-40 1 Weekmentioning
confidence: 99%
“…The mandible is highly sensitive to alterations in body bone mass density (BMD), and numerous studies have demonstrated a correlation between mandibular and skeletal (vertebral) bone densities [6][7][8]. Bone quality differs among individuals [9] and can be assessed on different types of radiographs. Various indexes are available for the assessment of mandibular bone quality assessment on panoramic X-rays, based on the manual measurement of anatomical structures [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, data from Asian populations is lacking. Reported ethnic variations in bone size, bone mineral density, craniofacial characteristics, differing dental disease patterns and other population specific characteristics may possibly impact residual ridge-remodeling patterns and resultantly residual alveolar bone heights (Lavelle 1973;Nelson & Megyesi 2004;Soh et al 2005;Wong et al 2007).…”
mentioning
confidence: 99%